Toothless Reforms? The Remarkable Stability of Female Labor Force Participation in a Top-Reforming Country - Norberto Pignatti; Karine Torosyan; Maka Chitanava (Institute of Labor Economics (IZA), 2016)
Low Female Labor Force Participation (FLFP) constitutes a foregone opportunity at both the macro and at the micro levels, potentially increasing the vulnerability of households and lowering the long-run development perspectives of a country. Most international organizations and national policy makers see low FLFP as a serious issue that needs to be addressed by adopting appropriate policies. We investigate the possible reasons of the remarkable stability of FLFP in a top-reforming upper-middle income country. Our goal is to in disentangle the different forces at work and to draw useful lessons for the design of participation-enhancing policies. Using data from a nationally representative Household Survey covering the period 2003-2015, we employ Blinder-Oaxaca (Blinder, 1973 and Oaxaca, 1973) type decomposition to decompose changes over time in FLFP levels into parts that are due to changes in observable factors versus changes in the strength of impact of these factors. This allows us to identify possible shifters of the FLFP rate and propose areas of special interest for policy making. We show that the stability of FLFP in Georgia during the period 2003-2013 is due to offsetting socio-economic changes taking place in the country, and that the increase in the last period covered by our dataset – 2013-2015 – can be attributed to the emergence of new labor opportunities for women. We conclude that, while useful, supply-side economic reforms are not sufficient to increase FLFP and need to be complemented by demand-side policies aiming at creating more and better work opportunities for women.
Keywords: J16; J18; J21; J24; P11; P21; P23; 330; employment; female labor force participation; labor market; public policy; reforms